Clinical and Genetic Characteristics of IKZF1 Mutation in Chinese Children With B-Cell Acute Lymphoblastic Leukemia - Zhang, Jingying; Xu, Xiao-Jun; Liu, Lixia; Song, Hua; Shen, Heping; Xu, Weiqun; Zhao, Fenying; Liang, Juan; Liao, Chan; Wang, Yan; Xia, Tian; Cao, Shanbo; et al. (Frontiers in Genetics, 2022)
Acute lymphoblastic leukemia (ALL) is a malignancy associated with altered lymphoid precursor hyperplasia and accompanied with different genetic mutations. Few studies have been reported on the association between gene mutations and clinical features of IKZF1 mutation in children with B-cell ALL (B-ALL). We investigated clinical and genetic characteristics in 200 newly diagnosed pediatric B-ALL through multiplex ligation-dependent probe amplification (MLPA) and targeted next-generation sequencing (NGS) method. We found that IKZF1 mutations, including large segment deletions, small insertions or deletions (InDels) and single nucleotide variations (SNVs), were detected in 22 patients with a positive mutation rate of 11.0%. IKZF1 mutation was significantly associated with higher WBC count (19.38×109/L vs. 5.80×109/L, P = 0.002). Compared with IKZF1 wild-type cases, a higher frequency of IL7R gene mutation was discovered in IKZF1 mutant cases (9.1% vs. 0.0%, P = 0.012). Patients with IKZF1 mutation were less sensitive to glucocorticoid induction than patients without IKZF1 mutation (54.5% vs. 9.0%, P < 0.001). On the 15th day of induction, minimal residual disease (MRD) >10-3 level were higher in IKZF1 mutant patients than wild-type patients (45.5% vs. 14.0%, P = 0.018). In conclusion, our study reveals the association between genetic mutations and clinical features in Chinese children with B-ALL, which might contribute to molecular classification, risk stratification and prognosis evaluation, and provide new ideas for targeted therapy in ALL.